Asas-Asas Umum Pemerintahan yang Baik dalam Pelayanan Publik - Solechan Solechan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract AAUPB (Asas asas umum pemerintahan yang Baik) has a long journey from the beginning of its birth in the Netherlands to its application in Indonesia today. AAUPB at first was only in the theoretical realm and then entered into law until AAUPB got a very important position in Law No. 30 of 2014. Initially, AAUPB was intended as a means of legal protection or rechtsbescherming and was even used as an instrument to increase legal protection or rechtsbescherming for citizens from government actions. AAUPB is then used as the basis for judgments in the judiciary and administrative efforts, as well as an unwritten legal norm for government actions The history of the development of AUPB in Indonesia can be seen from the development of the AUPB principle in various laws and regulations, the practice of implementing the AUPB in court decisions or jurisprudence and doctrine. The development of the AUPB principle arrangement had found an increasingly strong momentum when the Government Administration Act was passed in 2014. As a result of the adoption of the concept of the welfare state, the state must fulfill the welfare of the community, one of which is through public services. With the AAUPB, it is expected that the government as a public service provider, can accept the AAUPB as a legal norm that must be used as the basis by the civil service provider in carrying out its authority, as well as a means for citizens to sue deviant public service providers. Keywords: General principles of good governance, public service. Abstrak Asas-asas umum pemerintahan yang baik (selanjutnya disebut AAUPB) lahir dari praktik penyelenggaraan negara dan pemerintahan sehingga bukan produk formal suatu lembaga negara seperti undang-undang. Asas-asas umum pemerintahan yang baik dapat dipahami sebagai asas-asas umum yang dijadikan sebagai dasar dan tata cara dalam penyelenggaraan pemerintahan yang layak, yang dengan cara demikian penyelenggaraan pemerintahan itu menjadi baik, sopan, adil, dan terhormat, bebas dari kezaliman, pelanggaran peraturan, tindakan penyalahgunaan wewenang dan tindakan sewenang-wenang. Sejarah perkembangan AUPB di Indonesia dapat dilihat dari perkembangan prinsip AUPB dalam berbagai peraturan perundang-undangan, praktik penerapan AUPB dalam putusan pengadilan atau yurisprudensi serta doktrin. Perkembangan pengaturan prinsip AUPB menemukan momentumnya yang semakin kuat, tatkala UU Administrasi Pemerintahan disahkan pada tahun 2014. Sebagai akibat dari dianutnya konsepsi welfare state maka negara memiliki kewajiban untuk memenuhi kesejahteraan masyarakat salah satunya melalui pelayanan publik. Dengan adanya AAUPB diharapkan pemerintah sebagai pemberi pelayanan publik dapat menerima AAUPB sebagai norma hukum yang harus dijadikan dasar oleh penyelenggara pelayanan publik dalam menjalankan kewenangannya, sekaligus sarana bagi warga negara untuk menggugat penyelenggara pelayanan publik yang menyimpang. Kata Kunci : Asas-asas umum pemerintahan yang baik, Pelayanan Publik